1997
DOI: 10.1038/ng0597-44
|View full text |Cite
|
Sign up to set email alerts
|

HIP1, a human homologue of S. cerevisiae Sla2p, interacts with membrane-associated huntingtin in the brain

Abstract: Huntington disease (HD) is associated with the expansion of a polyglutamine tract, greater than 35 repeats, in the HD gene product, huntingtin. Here we describe a novel huntingtin interacting protein, HIP1, which co-localizes with huntingtin and shares sequence homology and biochemical characteristics with Sla2p, a protein essential for function of the cytoskeleton in Saccharomyces cerevisiae. The huntingtin-HIP1 interaction is restricted to the brain and is inversely correlated to the polyglutamine length in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
267
0
1

Year Published

1998
1998
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 347 publications
(276 citation statements)
references
References 45 publications
8
267
0
1
Order By: Relevance
“…Although there is some controversy about the role of htt aggregates, many authors propose, on the basis that Htt interacts with proteins associated to cytoskeleton-based transport (Li et al 1995;Kalchman et al 1997;Wanker et al 1997;Li et al 1998), that their presence in the neuropil is implicated in disturbances of axonal transport (Li et al 2001). Our present findings show that decreasing BDNF expression in the R6/1 mouse line increases the number of non-nuclear aggregates, which could be related to the enhanced dysfunction of dopaminergic neurons in bDM mice.…”
Section: Discussionsupporting
confidence: 54%
“…Although there is some controversy about the role of htt aggregates, many authors propose, on the basis that Htt interacts with proteins associated to cytoskeleton-based transport (Li et al 1995;Kalchman et al 1997;Wanker et al 1997;Li et al 1998), that their presence in the neuropil is implicated in disturbances of axonal transport (Li et al 2001). Our present findings show that decreasing BDNF expression in the R6/1 mouse line increases the number of non-nuclear aggregates, which could be related to the enhanced dysfunction of dopaminergic neurons in bDM mice.…”
Section: Discussionsupporting
confidence: 54%
“…[12][13][14][15][16] In several cases, the strength of Htt protein interactions has been shown to be affected by the length of polyQ tract, including the interaction with CREB binding protein, 7,9 HAP-1, 17 nuclear receptor co-repressor N-CoR, 18 Sp1 19 and others. 20,21 Rhes, a striatal-specific guanine nucleotide-binding protein, interacts preferentially with polyQ-expanded Htt and induces its sumoylation, leading to cytotoxicity.…”
Section: Resultsmentioning
confidence: 99%
“…The 110 kDa protein HIP1, for example, binds to Huntingtin, which suffers poly-glutamine expansions in Huntington's disease. 29,30 Recently, it has been suggested that mutated Huntingtin releases the HIP1 protein, which then is free to interact with another novel protein, Hippi. HIP1 and Hippi reportedly form a complex together with pro-Caspase-8, thereby triggering caspase activation and cell death.…”
Section: Discussionmentioning
confidence: 99%